The effect of 45 minutes of soccer-specific exercise on the performance of soccer skills - Stone, K. J.; Oliver, J. L. (International Journal of Sports Physiology and Performance, 2009)
Purpose: The aim of the study was to examine the effect of fatigue, developed during prolonged high-intensity intermittent exercise, on the performance of soccer shooting and dribbling skill. Methods: Nine semiprofessional soccer players with a mean age of 20.7 ± 1.4 years volunteered to participate in the study. Participants completed a slalom dribble test and the Loughborough Soccer Shooting Test (LSST), before and directly following the performance of three 15-min bouts of a modified version of the Loughborough Intermittent Shuttle Test (LIST). Results: Mean heart rates and mean 15-m sprint times remained unchanged across the three bouts of the LIST. Following the LIST slalom dribbling time increased significantly by 4.5 ± 4.0% (P = .009), while the mean total points scored during the LSST was significantly reduced by 7.6 ± 7.0 points (P = .012). When fatigued the frequency of shots in the LSST achieving the highest score of 5 points was reduced by 47% while the frequency of shots achieving the lowest 0 point score increased by 85%. Conclusion: Results show that while 45 min of exercise caused no decrements in sprint performance there were significant reductions in the ability to perform soccer-specific skills. Both the speed (dribbling time) and accuracy (shot performance) with which soccer-specific skills were executed was impaired following exercise replicating one-half of a soccer match.